Land settlement planning for improved irrigation management: a case study of the Kirindi Oya Irrigation and Settlement Project - Stanbury, P. (International Irrigation Management Institute, 1989)
This paper analyzes the impact of settlement policies on irrigation management in a new irrigated settlement scheme in southern Sri Lanka based on field research in 1988. It provides policy recommendations for improvements on this scheme and in future schemes.